Universal pion freeze-out in heavy-ion collisions - Adamová, Dagmar; Appelshäuser, Harald; Braun-Munzinger, Peter; Damjanović, Sanja; Dietel, Thomas; Dietrich, Lars; Drees, Axel; Esumi, ShinIchi; Filimonov, Kirill; Glässel, Peter; Lenkeit, Björn; Dubitzky, Wilrid; et al. (Arxiv, 2002)
Based on an evaluation of data on pion interferometry and on particle yields at mid-rapidity, we propose a universal condition for thermal freeze-out of pions in heavy-ion collisions. We show that freeze-out occurs when the mean free path of pions lambda_f reaches a value of about 1 fm, which is much smaller than the spatial extent of the system at freeze-out. This critical mean free path is independent of the centrality of the collision and beam energy from AGS to RHIC.
Gesehen am 28.02.2018